ANALISIS PENGARUH DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA MUSEUM TEKSTIL JAKARTA - Magdalena Merry Andany; Roels Ni Made Sri Puspadewi (CV. ADIBA AISHA AMIRA, 2023)
This research was conducted with the aim of describing how much influence tourist attraction has on tourists' visiting decisions at the Jakarta Textile Museum. This study used a quantitative method which was distributed to 100 respondents who had visited the Textile Museum. The research data obtained was processed using SPSS 25 software. Analysis of research data used descriptive statistical analysis tests, simple linear regression analysis, classical assumption test, t-test, and coefficient of determination test. Researchers also conducted brief interviews with museum managers to find out more in-depth information regarding the attractiveness of the Jakarta Textile Museum. The results showed that the decision to visit tourists at the Jakarta Textile Museum was influenced by 55.5% by tourist attractions, while others were influenced by other factors not examined in this study. The results of the simple linear regression test show a significance value of 0.000 <0.05, which means that there is an influence between the tourist attraction variables. The results of the t test show that the t value is 11.045 > 1.984, which means that there is a significant influence between the variable tourist attraction and the decision to visit tourists at the Jakarta Textile Museum.